Application of Audiolingual Method in Active Arabic Language Learning for Visually Impaired Students - Ridwan Efendi; Nurul Wahdah; Kamaludin Kamaludin; Ali Sadikin; Asmawati Asmawati; Sardimi Sardimi (Universitas Islam Negeri Palangka Raya, 2023)
This study investigates the effectiveness of the Audiolingual Method in teaching Arabic to visually impaired students at Tahfidz Sam'an Boarding School in Darussudur Cimenyan, Bandung. The method, focusing on listening and speaking skills, is adapted to suit the unique needs of visually impaired learners. Using a qualitative approach with participant observations and interviews, the researchers assess the impact on students' language proficiency. Preliminary findings suggest positive outcomes, enhancing engagement, fostering inclusivity, and promoting a more interactive Arabic language learning environment. The study also incorporates teachers' perspectives, offering valuable insights for adapting language teaching methods to cater to the specific requirements of visually impaired students, ultimately contributing to effective Arabic language education in Islamic boarding schools.